2021
DOI: 10.1101/2021.01.25.427846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 receptor binding mutations and antibody mediated immunity

Abstract: SARS-CoV-2 mutations can impact infectivity, viral load, and overall morbidity/mortality during infection. In this analysis, we look at the mutational landscape of the SARS-CoV-2 receptor binding domain, a structure that is antigenic and allows for viral binding to the host. We analyze 104193 GISAID sequences acquired on October 15th, 2020 with a majority of sequences (96%) containing point mutations. We report high frequency mutations with improved binding affinity to ACE2 including S477N, N439K, V367F, and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown that this mutation increases affinity of the S glycoprotein for ACE-2 (Nelson et al, 2021) and confers resistance to neutralization mediated by monoclonal antibodies (mAbs) and plasma from naturally infected and vaccinated individuals (Ku et al, 2021;Stamatatos et al, 2021;Tada et al, 2021;Wang et al, 2021). The S477N mutation confers a higher affinity for the ACE-2 receptor and has rapidly spread to many countries in Oceania and Europe (Flores-Alanis et al, 2021;Hodcroft et al, 2020;Jolly et al, 2021;Mejdani et al, 2021;West et al, 2021;Wu et al, 2021). The S477N and N501S mutations are found in several SARS-CoV-2 genomes in Quebec (S.M.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that this mutation increases affinity of the S glycoprotein for ACE-2 (Nelson et al, 2021) and confers resistance to neutralization mediated by monoclonal antibodies (mAbs) and plasma from naturally infected and vaccinated individuals (Ku et al, 2021;Stamatatos et al, 2021;Tada et al, 2021;Wang et al, 2021). The S477N mutation confers a higher affinity for the ACE-2 receptor and has rapidly spread to many countries in Oceania and Europe (Flores-Alanis et al, 2021;Hodcroft et al, 2020;Jolly et al, 2021;Mejdani et al, 2021;West et al, 2021;Wu et al, 2021). The S477N and N501S mutations are found in several SARS-CoV-2 genomes in Quebec (S.M.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that this mutation increases affinity of the S glycoprotein for ACE-2 18 and confers resistance to neutralization mediated by mAbs and plasma from naturally-infected and vaccinated individuals 19–22 . The S477N mutation confers a higher affinity for the ACE-2 receptor and has rapidly spread to many countries in Oceania and Europe 2328 . The S477N and N501S mutations are found in several SARS-CoV-2 genomes in Quebec (Laboratoire de Santé Publique du Québec, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…A701V, shared by variant B.1.351 [100], is in the S2 subunit adjacent to the furin cleavage site [219] and may impact SARS-CoV-2 cleavability and infectivity. S477N, also found in variant 20A.EU2, increases binding to hACE2 [221,222] and reduces antibody-mediated neutralization [178,223], likely due to its position within a neutralizing epitope [224]. D614G and E484K are shared with multiple other variants (Table 5 [183,225].…”
Section: Other Variants Of Interestmentioning
confidence: 99%